Psychological well-being of Incarcerated women in J&K - Hyder , Asma; Sharma, Neeru (International Journal of Psychosocial Rehabilitation, 2020)
Women in penitentiary create a small section of the number of Women convicts who pass through the criminal justice’s system each year. Their delinquencies often come at great cost to society, their kin and themselves. However, Women criminals do not pose a peril to society, most have multiple intricate requirements and many are caught in a detrimental cycle of exploitation, victimisation and felonious. Operational imprisonment severely affects the psychological well-being of women prisoners. Due to low prevalence of female delinquency there is less importance to research on this field. There is insufficient data and research on the problems of women convicts, thus this paper is an attempt to study psychological health of incarcerated women. The reviewed literature indicates that there is a high rate of serious mental health problems among imprisoned women, particularly among those who are associated with drug abuse, psychosis, affective disorder, obsessive-compulsive disorder and post traumatic stress. This paper will help in suggesting specific programmes for women offenders that its effectiveness will focus on higher risk of crime committed by women.